Kontribusi Hukum Islam dalam Pembangunan Ekonomi di Indonesia - ferli, As; Winarti, Tri (Mu’amalah: Jurnal Hukum Ekonomi Syariah, 2022)
Islam, as a divine religion revealed to Prophet Muhammad through the angel Jibril, has provided comprehensive guidance for human life, from general matters to specific aspects. One of the key areas addressed in this paper is the foundation and principles that underpin the development of Islamic economics, particularly in Indonesia. This study aims to examine the impact and contribution of Islamic law in shaping Islamic economic development in Indonesia. Islamic law serves as a guiding framework for human life, especially in economic activities, which are integral to daily existence. The paper explores how humans can optimize their intellect and conscience in aligning their actions with the teachings of Islam in economic practices. Specifically, it emphasizes the importance of justice, fairness, and public benefit as essential elements of Islamic economic development. The pursuit of profit at the expense of others' welfare has led to dissatisfaction and unrest, highlighting the need for a system that prioritizes collective well-being. By maximizing natural resources and human resources in accordance with Islamic principles, a just and prosperous society can be achieved. This paper aims to raise awareness about the responsible stewardship of resources, ensuring sustainable development for future generations in line with Islamic teachings.